Policies for higher education in Colombia: the effects of contemporary governance - Díaz Flórez, Olga Cecilia (Universidade Estadual de Campinas, 2016)
This article contextualize social and educational policies in the forms of government intervention characterized by a pragmatism at keeps the suction set "friendly approaches to the market" which will swing less to greater coordination between them. These reforms, which are governed by the growth stimulated by the market are based on government practices, which combine two important strategies that provide flexibility: the global frame design with different ways to achieve the focused objectives in the growth and use of OMCs operating with a degree of variability which are monitored through regular monitoring ongoing for several organizations and social partners. Thus, the purpose of this discussion is to understand the place of politics in contemporary forms of government, analyzing both the scope as the questions related to the reform process driven by the Bologna Declaration. Besides this, the debate deepens the affectations of policies generated in countries like Colombia, showing how one of its most visible effects is presented by the guidelines for skills and the mass evaluation, conceived as a strategic place, as a kind of hinge, which seeks to articulate the world education with the productive sector. To illustrate some of the effects produced by these strategies of government, the text also thematizes the new issues raised, particularly the level of hierarchy, stratification and inequality derived from forms of social regulation undertaken in higher education that took place in Colombia in the last decade. In conclusion presents a few current guidelines from the environment experienced in recent years in the country, showing that a reform in higher education confirms this trend .; but it managed to contain this movement thanks to the active role of the student movement which secured the transforming role of education, the nature of the common good that belongs to all of society making possible the opportunity to provide a dignified life for most.